A minimalist and robust chemo-photothermal nanoplatform capable of augmenting autophagy-modulated immune response against breast cancer. (June 2022) - Ming, Hui; Li, Bowen; Tian, Hailong; Zhou, Li; Jiang, Jingwen; Zhang, Tingting; Qiao, Ling; Wu, Peijie; Nice, Edouard C.; Zhang, Wei; He, Weifeng; Huang, Canhua; et al.
Abstract: Previously used in anti-fungal therapy, itraconazole has now been shown to be successful in treating advanced breast cancer (NCT00798135). However, its poor solubility still restricts its application in clinical treatment. There is therefore an urgent need for combined methods to enhance the therapeutic effect of itraconazole (IC) in breast cancer treatment. With this goal, co-assembled IC/IR820 NPs with synergistic photonic hyperthermia and itraconazole payloads have been constructed to overcome these shortcomings. The IC/IR820 NPs show an enhanced therapeutic effect on breast cancer by inducing reactive oxygen species (ROS)-mediated apoptosis and autophagic death. Further evaluation in a mouse model has shown impressive effects of the IC/IR820 NPs on both inhibiting tumor metastasis and activating immunity to prevent tumor recurrence. Mechanistically, itraconazole may promote both tumor cell antigen presentation through autophagy and the activation of dendritic cells to induce an immune response, which displays a synergistic effect with the immune response generated by photothermal therapy to inhibit tumor recurrence. This strategy of combining itraconazole and IR820 into one minimalist and robust nanoplatform through co-assembly results in excellent therapeutic efficacy, suggesting its potential application as an alternative method for the clinical treatment of breast cancer. Graphical abstract: The preparation of the IC/IR820 NPs allows amplified apoptosis, autophagy, and immunogenic cell death during breast cancer therapy. Created with BioRender.com . Image 1